2007
DOI: 10.1111/j.1574-6968.2007.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

YddG fromEscherichia colipromotes export of aromatic amino acids

Abstract: The inner membrane protein YddG of Escherichia coli is a homologue of the known amino acid exporters RhtA and YdeD. It was found that the yddG gene overexpression conferred resistance upon E. coli cells to the inhibiting concentrations of l-phenylalanine and aromatic amino acid analogues, dl-p-fluorophenylalanine, dl-o-fluorophenylalanine and dl-5-fluorotryptophan. In addition, yddG overexpression enhanced the production of l-phenylalanine, l-tyrosine or l-tryptophan by the respective E. coli-producing strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 17 publications
0
63
0
Order By: Relevance
“…2), (ii) disruption of the ygaW gene in the non-L-alanine-metabolizing mutant MLA301 resulted in intracellular accumulation and a reduced export rate of L-alanine in the presence of extracellular Ala-Ala (Fig. 3), (iii) yddG (9) and yeaS (26) have been characterized to encode exporters for L-aromatic amino acids and L-leucine, respectively, but not for L-alanine, (iv) disruption of the ytfF gene in MLA301 did not lead to a change in the The non-L-alanine-metabolizing strain MLA301 was incubated in minimal medium with (lanes 3, 5, 7, 9, and 11) or without (lanes 2, 4, 6, 8, and 10) 6 mM Ala-Ala. After a 5-min incubation, total RNA isolation and RT-PCR were performed as described in Materials and Methods. Lane 1, molecular size marker in base pairs; lanes 2 and 3, ygaW; lanes 4 and 5, ytfF; lanes 6 and 7, yddG; lanes 8 and 9, yeaS; lanes 10 and 11, gapA.…”
Section: Discussionmentioning
confidence: 99%
“…2), (ii) disruption of the ygaW gene in the non-L-alanine-metabolizing mutant MLA301 resulted in intracellular accumulation and a reduced export rate of L-alanine in the presence of extracellular Ala-Ala (Fig. 3), (iii) yddG (9) and yeaS (26) have been characterized to encode exporters for L-aromatic amino acids and L-leucine, respectively, but not for L-alanine, (iv) disruption of the ytfF gene in MLA301 did not lead to a change in the The non-L-alanine-metabolizing strain MLA301 was incubated in minimal medium with (lanes 3, 5, 7, 9, and 11) or without (lanes 2, 4, 6, 8, and 10) 6 mM Ala-Ala. After a 5-min incubation, total RNA isolation and RT-PCR were performed as described in Materials and Methods. Lane 1, molecular size marker in base pairs; lanes 2 and 3, ygaW; lanes 4 and 5, ytfF; lanes 6 and 7, yddG; lanes 8 and 9, yeaS; lanes 10 and 11, gapA.…”
Section: Discussionmentioning
confidence: 99%
“…Protein structure prediction using the protein homology/analogy recognition engine (PHYRE) search tool suggests that STM1530 is a porin similar to Klebsiella pneumoniae OmpK36, E. coli PhoE, and E. coli OmpF. It has been reported that in S. enterica serovar Typhimurium, the porin OmpD together with a putative inner membrane efflux pump, YddG, is involved in resistance to methyl viologen and aromatic amino acids (8,32). In addition, it has been suggested that OmpD in S. enterica serovar Typhimurium interacts with the periplasmic protein YdeI/ OmdA to increase resistance to antimicrobial peptides (29).…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids containing the P nlp -driven cysM gene and chloramphenicol resistance marker flanked by the attachment sites of the Mu phage, designed for inducing mini Mu-mediated integration, were introduced by electroporation into strain SC17, which harbored the helper plasmid pMH10 (51) that expressed Mu transposase. Mumediated chromosomal integration was induced according to previously described methods (34,52). Strains with the chromosomal P nlp -cysM cassettes were selected on an agar plate containing chloramphenicol.…”
Section: Plasmid Name Vectormentioning
confidence: 99%